Decoding collagen’s thermally induced unfolding and refolding pathways - Alaa Al-Shaer; Nancy R. Forde (Proceedings of the National Academy of Sciences, 2025)
Collagen has been evolutionarily selected as the preferred building block of extracellular structures. Despite inherent thermodynamic instability of individual proteins at body temperature, collagen manages to assemble into higher-order structures that provide mechanical support to tissues. Sequence features that enhance collagen stability have been deduced primarily from studies of collagen-mimetic peptides, as collagen’s large size has precluded high-resolution studies of its structure. Thus, methods are needed to analyze the structure and mechanics of full-length collagen proteins. In this study, we used AFM imaging to investigate the thermal response of collagen type IV, a key component of basement membranes. We observed a time-dependent loss of folded structures upon exposure to body temperature, with structural destabilization along the collagenous domain reflected by shorter contour lengths (seen also for collagens type I and III). We characterized the sequence-dependent bending stiffness profile of collagen IV as a function of temperature and identified a putative initiation site for thermally induced unfolding. Interchain disulfide bonds in collagen IV were shown to enhance thermal stability and serve as primary nucleation sites for in vitro refolding. In contrast to the canonical C-to-N-terminal folding direction, we found an interchain cystine knot to enable folding in the opposite direction. A multiple sequence alignment revealed that this cystine knot is evolutionarily conserved across metazoan phyla, highlighting its significance in the stabilization of early collagen IV structures. Our findings provide mechanistic insight into the unfolding and refolding pathways of collagen IV, and how its heterogeneous sequence influences stability and mechanics.